Comparative Analysis of the Cell Fates of Induced Schwann Cells from Subcutaneous Fat Tissue and Naïve Schwann Cells in the Sciatic Nerve Injury Model. (20th June 2017) - Zhang, Mingzi; Jiang, Mei Hua; Kim, Dae-Wook; Ahn, Woosung; Chung, Eunkyung; Son, Youngsook; Chi, Guangfan
Abstract : Purpose . The fate and function of the induced Schwann cells (iSCs) like cells from adipose tissue have not been critically evaluated in vivo after transplantation. The objective of this study is to compare the fate of iSCs with naïve SCs (nSCs) after transplantation into the lesion sites of sciatic nerve, respectively. Methods . Adipose-derived stem cells from eGFP-expressing transgenic rat's subcutaneous fat were induced to iSCs in vitro. iSCs were injected to the sciatic nerve lesion area after crush injury and the cells fate was comparatively analyzed with that of nSCs from the same rat. Results . At 12 weeks after transplantation, nSCs were detected only in the restricted area of cell transplantation site but iSCs were widely distributed all over the sciatic nerve. Based on double fluorescence observations, both iSCs and naïve ones were colocalized with P0-expressing myelin sheath, outbound by laminin-expressing basal membrane, and terminated at contactin-associated protein-expressing doublets. However, some of iSCs were also differentiated to the fibrocyte/fibroblast-like cells. In the histological analysis of repaired sciatic nerves, axon density was higher in iSC-received group than in the nSCs group and normal sciatic nerve. Conclusion . iSCs induced from subcutaneous fat tissues have higher engraftment and migration capacity than nSCs.